An Introduction to Implementing the Treaty on the Prohibition of Nuclear Weapons. Issue 1 (2nd January 2021) - Borrie, John
ABSTRACT: The 2017 Treaty on the Prohibition of Nuclear Weapons (TPNW) is a significant international achievement, although it faces opposition from the nuclear-armed states and some of their allies because it is intended to create impetus for a transition away from nuclear weapons, on which they rely for security. Now that the TPNW has entered into force internationally, its stakeholders face a range of practical decisions and other questions related to how to implement its provisions and build a sustainable multilateral regime that will contribute to the treaty's overall goals. This article, by the issue's guest editor, provides context for the TPNW's emergence and the main categories of literature that have emerged on different aspects of the new regime, including some of the major TPNW-related debates. The article further outlines how each of the other thematic contributions to this journal issue fit within it and relate to each other. These include research articles on matters related to national implementation, treaty compliance for nuclear-armed states eventually wishing to join the TPNW, universalization, and building a sustainable treaty management culture. Commentaries from academic experts, the Red Cross and Red Crescent Movement and civil society activists round out the issue.